INNOVATIVE METHODS AND APPROACHES FOR DEVELOPING CREATIVE THINKING IN FOREIGN LANGUAGE CLASSES (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2026)
This article explores the significance of fostering creative thinking skills within the framework of foreign language teaching and analyzes the most effective innovative methods in this field. Unlike traditional pedagogical approaches, modern language education demands not only linguistic competence but also the ability to find creative solutions in problematic contexts. During the research, the effectiveness of methods such as "Brainstorming," "Synectics," and "Mind Mapping" was scientifically substantiated. Furthermore, the article presents the results of experimental trials through comparative tables and develops methodological recommendations aimed at increasing lesson efficiency.